Periodontal Barrier Membranes: A Review with Case Report - Gupta, K. K.; Srivastava, Amitabh; Kumar, Vinod; Kumar, Snehi (Journal of Membrane and Separation Technology, 2013)
Periodontal regeneration is healing after periodontal surgery that results in the formation of new attachment apparatus, consisting of cementum,periodontal ligament(PDL) and alveolar bone. Although the goal of complete and predictable regeneration still remains elusive, many techniques and materials have been developed that show good clinical and histologic outcomes.Advancements in periodontal regenerative armamentarium have encouraged clinicians to aggressively seek this therapeutic goal. Guided tissue regeneration (GTR) is effective in halting tissue and bone destruction and promoting new tissue and bone formation. Reconstructive dental professionals are constantly looking for an edge that jump starts the healing process to maximize predictability as well as quality and quantity of regenerated bone.